THE ISSUE OF SCIENTIFIC DEFINITION OF THE CONCEPT OF DIGITAL ECONOMY - Kotelevets D.О. (The actual problems of regional economy development, 2022)
The purpose of the article is to identify the place of the digital economy in a broad terminological space. To achieve this goal, general scientific and specific research methods were used, namely: content analysis and monographic method - to study scientific approaches to the interpretation of different types of economic systems; methods of synthesis and systematization - to summarize the results of the study of definitions formulated by foreign and Ukrainian scientists; methods of scientific abstraction and analysis - to identify similarities and differences in scientific approache to the interpretation of digital economys. The study of development trends and features of the digital economy requires a priority definition of its essence, and, accordingly, the study of existing scientific approaches to interpretation. The article analyzes some scientific approaches to the interpretation of the essence of the information society, information economy, knowledge economy, innovation economy, as well as highlights their main characteristics. The study allowed to correlate the concept of digital economy with the above categories, to show their interdependence or subordination. The emphasis of the article is put on the definition of synonymous concepts and terms that are interrelated. This allowed author to distinguish the digital economy as a completely independent economic category, interpreted as a new type of economic system, within which the processes of production, exchange, distribution and consumption are based on modern information technology, and its main actors are able to generate, transfer and use effectively information resources. Author concluded that digital economy is a type of economic system based on information generated by intellectual resources and knowledge, and determined by the development of innovative information technologies, the introduction of which into the activities of economic entities leads to the transformation of their business models, economic processes and channels of communication with stakeholders. Prospects for further research are the study of the main factors of development of the digital economy.